Інноваційні підходи модернізації управління фінансовою безпекою банку - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Масюк, Юлія Воловимирівна; Masiuk, Yuliia; Брусенцева, А. В.; Brusentseva, A. (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2024)
Стаття присвячена дослідженню інноваційних аспектів модернізації управління фінансовою безпекою банківських установ. Авторами визначені елементи організації фінансової безпеки банківських установ. Організація фінансової безпеки банківських установ має бути направлена на комплекс заходів, спрямованих на захист банку від внутрішніх і зовнішніх загроз, які можуть вплинути на його фінансову стабільність, репутацію та ефективність діяльності. Основні зав-дання полягають в управлінні ризиками, запобіганні шахрайству, забезпеченні кібербезпеки та дотриманні регуляторних вимог. Дослідження інноваційних аспектів модернізації управління фінансовою безпекою банківських установ є важливим елементом для забезпечення стабільності та ефективної роботи фінансових організацій в умовах зростаючих ризиків та глобальної цифровізації. Інновації в управлінні фінансовою безпекою сприяють покращенню моніторингу ризиків, підвищенню ефективності операцій та забезпеченню захисту від зовнішніх та внутрішніх загроз. Організація управління активами і пасивами банку є стратегічно важливою частиною його діяльності, оскільки вона забезпечує ліквідність, фінансову стійкість і максимізацію прибутковості. Ефективне управління активами і пасивами допомагає банку знижувати ризики, адаптуватися до змін на ринку та забезпечувати дотримання регуляторних вимог. Це, в свою чергу, сприяє підтримці довіри клієнтів і забезпечує стабільний розвиток банківської установи. The article is devoted to the study of innovative aspects of modernization of financial security management of banking institutions. The authors defined elements of the organization of financial security of banking institutions. The organization of financial security of banking institutionsshould be directed to a set of measures aimed at protecting the bank from internal and external threats that may affect its financial stability, reputation and operational efficiency. The maintasks are risk management, fraud prevention, cyber security and regulatory compliance. The study of innovative aspects of the modernization of financial security management of banking institutions is an important element for ensuring the stability and efficient operation of financial organizations in the conditions of growing risks and global digitalization. Innovations in the management of financial security contribute to the improvement of risk monitoring, increasing the efficiency of operations and ensuring protection against external and internal threats. The organization of the bank's asset and liability management is a strategically important part of its activity, as it ensures liquidity, financial stability and maximization of profitability. Effective management of assets and liabilities helps the bank to reduce risks, adapt to changes in the market and ensure compliance with regulatory requirements. This, in turn, contributes to the maintenance of customer trust and ensures the stable development of the banking institution. In banking institutions working with foreign currency, there are currency risks associated with exchange rate fluctuations. Therefore, various hedging instruments such as forwards, futures and currency swaps are used to reduce these risks. Also, commercial banks can reduce currency risks by holding assets in different currencies, which helps minimize the impact of fluctuations in one particular currency. Innovative technologies play a significant role in ensuring the stability of banking institutions and increasing the financial stability of banks against external and internal threats. Such technologies allow not only to reduce risks, but also increase the efficiency of financial resources management, improve interaction with clients and facilitate flexible response to changes in financial markets.
Innovative approaches to mod ernization of bank financial security management
Keywords: інновації; innovations; модернізація; modernization; управління; management; фінансова безпека; financial security